Development of non-enzymatic glucose biosensor based on conducting polymer nanocomposite films fabricated by electrochemical technique / Ali Mohamad Ali Abdul Amir - Ali Mohamad , Ali Abdul Amir (2017)
Different analytical principles have been adopted for monitoring blood glucose levels which include spectrophotometry and electrochemical methods. Out of these, electrochemical methods are highly reliable, simple and sensitive. Non-enzymatic procedures are preferred over enzymatic methods since it overcomes the serious problem of storage stability of enzyme based sensors. Non-enzymatic method utilizes direct electrooxidation of glucose on the surface of electrodes. Nanomaterials are used as electrocatalysts to modify sensor electrodes and achieve greater electrochemical response. In the present work, polypyrrole conducting polymer/chitosan-based non-enzymatic glucose biosensors using Fe3O4 and TiO2 as nanomaterials in one-step electrodeposition technique have been developed. Conducting polymer nanocomposite films prepared on ITO glass electrode by cyclic voltammetry were characterized by FTIR, XRD, SEM, HR-TEM, and XPS. All these characterizations confirm the formation of Ppy-CS-metal oxide nanocomposite films. The oxidation potential of +0.18V (vs Ag/AgCl) and +0.13V (vs Ag/AgCl) as determined from cyclic voltammetry were applied on the sensor electrode of Ppy-CS-Fe3O4 and Ppy-CS-TiO2, respectively, for the amperometric determination of glucose in 0.1 M NaOH. A highly selective and sensitive non-enzymatic glucose sensor with wide detection range were fabricated with the detection range of 1 mM to 16 mM, and 1 mM to 14 mM for (Ppy-CS-Fe3O4/ITO) and (Ppy-CS-TiO2/ITO), respectively, with a fast response time of 3 seconds. This work has presented the role of nanomaterials and described the easy process of their homogenous distribution in the Ppy-CS composite films by one-step electrochemical process where all the components are taken in one solution in the electrochemical cell. The vital role of the nanomaterials is well realized in the glucose sensor due to the homogenous distribution of nanomaterials in the polymer films from this one-step deposition technique. Glucose was detected in common physiological interfering biomolecules such as uric acid, ascorbic acid, and cholesterol where the biomolecules were found to have no interference. The results exposed that the present sensor possesses a good selectivity and sensitivity towards the glucose detection. Additionally, the modified electrode has showed an excellent stability towards glucose sensing upon exposure in the environment for several days.